2014
DOI: 10.1590/1678-69712014/administracao.v15n3p101-131
|View full text |Cite
|
Sign up to set email alerts
|

As alianças estratégicas no picadeiro da arte/negócio circense

Abstract: O objetivo do artigo é estudar a contribuição das alianças para a longevidade das empresas, tendo como objeto um campo quase esquecido pela administração, as organizações circenses. A despeito de sua importância econômica e simbólica, tal setor é pouco estudado sob o ponto de vista de suas práticas gerenciais. Nesse sentido, o problema proposto para exame é identificar em que medida as unidades pesquisadas realizam alianças capazes de gerar benefícios competitivos. O foco de investigação são as parcerias com l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…In a recent study, Quaresma Jr., Silva and Carrieri (2014) focused on circus strategies in which circuses establish formal and informal partnerships with the media products of the cultural industry in order to achieve economic gains and a competitive edge in the entertainment market. To a certain extent, these authors have confirmed what Oliveira and Cavedon (2013, p.156) had found concerning "the establishment of associative networks between circuses and companies, due to the existence of demand for artistic activities by the market.…”
Section: Administration and Circus Organizationsmentioning
confidence: 99%
“…In a recent study, Quaresma Jr., Silva and Carrieri (2014) focused on circus strategies in which circuses establish formal and informal partnerships with the media products of the cultural industry in order to achieve economic gains and a competitive edge in the entertainment market. To a certain extent, these authors have confirmed what Oliveira and Cavedon (2013, p.156) had found concerning "the establishment of associative networks between circuses and companies, due to the existence of demand for artistic activities by the market.…”
Section: Administration and Circus Organizationsmentioning
confidence: 99%
“…The use of such attractions in large and structured circuses occurs formally, under agreements that establish how the circus can use a given product from popular media (Quaresma, Silva, & Carrieri, 2014). In smaller circuses, however, the use of these attractions is done informally, with covers, without any license or right of authorship, as R067 ironically suggests.…”
Section: Roaming: An Ancient Trick To Go Up In the Worldmentioning
confidence: 99%
“…The itinerancy of the circuses surveyed in this study allows circus subjects to alter their plans along their respective trajectories and negotiate their reality, which is mediated by the other plans created by individuals or groups encountered along the way. Parker (2011), Quaresma, Silva, andCarrieri (2014) and Aguiar and Carrieri (2016) have demonstrated that without a fixed address or headquarters to which an organization may return, its management is metamorphosed based on power relations, land conditions, and legal impositions by municipal bodies, the lack of an audience, weather conditions, etc. Meanwhile, improvisation is based on the circus art tradition, that is, the know-how of those living and working in the circus and interacting with the most varied audiences.…”
Section: Introductionmentioning
confidence: 99%